The WNT/β-catenin signaling in the context of odontogenic cysts and tumors: an update - Polti , Lucas Fabian; Felix , Fernanda Aragão; Souza , Mariana Silveira; Sousa , Rafael Aguiar de; Araujo , Gabriela Ribeiro de; Sousa, Silvia Ferreira de (Journal of Oral Diagnosis, 2025)
The Wnt/β-catenin signaling pathway is tightly controlled under typical physiological conditions, being involved in teeth developmental processes. Its dysregulation and the abnormal activation of downstream target genes can result from mutations in essential pathway components. These dysregulations might ultimately foster odontogenic cysts and tumors onset and progression. In this review, we retrieve the main alterations reported in the Wnt/β-catenin signaling pathway in the context of odontogenic cysts and tumors. Increasing evidence supports the involvement of the Wnt/β-catenin pathway disruption in the biology of calcifying odontogenic cyst, odontoma, adenoid ameloblastoma, and ghost cell-containing odontogenic tumors. A deeper understanding of these molecular mechanisms may contribute to improved diagnostic and therapeutic strategies in the future.